Comparison of the clinical efficacy of lateral versus medial unicondylar replacement for unicompartmental osteoarthritis of the knee: a meta-analysis - Haowei Bai; Pengyu Liu; Hao Li; Jiaju Yang; Zhitong Li; Qidong Guo; Min Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This meta-analysis evaluates the comparative efficacy of lateral unicompartmental arthroplasty (UKA) versus medial UKA in treating unicompartmental knee osteoarthritis (KOA). Methods We systematically searched Cochrane, PubMed, Embase, and Web of Science databases from January 2000 to September 2024. Literature screening, quality assessment, and data extraction were conducted based on predefined inclusion and exclusion criteria. Review Manager 5.4 software was used to analyze postoperative functional scores, pain scores, aseptic loosening, progression of contralateral arthritis, and prosthesis survival. Results Fifteen cohort studies, encompassing 2,592 knees with medial UKA and 614 knees with lateral UKA, were included. The analysis showed no statistically significant differences in functional scores [SMD = 0.11, 95% CI (− 0.10, 0.33), I2 = 64%, P = 0.31], pain scores [SMD = 0.23, 95% CI: (− 0.22, 0.67), I2 = 91%, P = 0.32], aseptic loosening [OR = 1.33, 95% CI: (0.31, 5.78), I2 = 0%, P = 0.70], progression of contralateral arthritis [OR = 0.37, 95% CI: (0.07, 1.91), I2 = 0%, P = 0.23], short- to intermediate-term survival [OR = 1.40, 95% CI: (0.84, 2.35), I2 = 0%, P = 0.20], and long-term survival [OR = 1.12, 95% CI: (0.61, 2.05), I2 = 0%, P = 0.70]. Conclusion Our findings indicate no significant differences in functional outcomes, pain relief, aseptic loosening, progression of contralateral arthritis, or prosthesis survival between lateral and medial UKA. Thus, both approaches are reliable options for patients with unicompartmental KOA.